1977
DOI: 10.1159/000144871
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of the uterine epithelium of mice treated neonatally with estrogen

Abstract: In neonatally estrogenized mice, uterine epithelial cells possessed a few microvilli on the fuzzy-appearing apical surface, regardless of the presence or the absence of estrogen. The cells showed well-developed rough endoplasmic reticulum and a large number of mitochondria, suggesting that the cells were actively functioning. At 13 months of age, the uterine epithelium of neonatally estrogenized mice was sometimes stratified and squamous. Spherical basal cells like those appearing in cancerous vagina in estrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1979
1979
1990
1990

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Immediate effects of estrogens on the developing uterus include qualitative and quantitative changes in protein synthesis (Newbold et al, 1981(Newbold et al, , 1984 and stimulation of epithelial proliferation (Forsberg, 1970;Eide, 1975a,b;Bigsby and Cunha, 1986). In adult mice treated neonatally with estrogen, the uterine epithelium may ex-Q 1989 ALAN R. LISS, INC press cystic hyperplasia (Takasugi et al, 1970;Yasuda et al, 1977;Rustia and Shubik, 1976;McLachlan et al, 1980;McLachlan and Fabro, 1982;Wordinger and Morrill, 1985) and/or squamous metaplasia (Dunn and Green, 1963;Takasugi and Bern, 1964;Rustia and Shubik, 1976;Yasuda et al, 1977;Mori, 1977;Vorherr et al, 1979;Baggs et al, 1980;Ennis and Davies, 1982;Wong et al, 1982;Walker 1980Walker , 1983Ostrander et al 1985). These proliferative lesions may progress to uterine adenocarcinoma (Rustia and Shubik, 1976;Napalkov and Anisimov, 1979;Vorherr et al, 1979;McLachlan et al, 1980;Gilloteaux et al, 1982;Walker, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Immediate effects of estrogens on the developing uterus include qualitative and quantitative changes in protein synthesis (Newbold et al, 1981(Newbold et al, , 1984 and stimulation of epithelial proliferation (Forsberg, 1970;Eide, 1975a,b;Bigsby and Cunha, 1986). In adult mice treated neonatally with estrogen, the uterine epithelium may ex-Q 1989 ALAN R. LISS, INC press cystic hyperplasia (Takasugi et al, 1970;Yasuda et al, 1977;Rustia and Shubik, 1976;McLachlan et al, 1980;McLachlan and Fabro, 1982;Wordinger and Morrill, 1985) and/or squamous metaplasia (Dunn and Green, 1963;Takasugi and Bern, 1964;Rustia and Shubik, 1976;Yasuda et al, 1977;Mori, 1977;Vorherr et al, 1979;Baggs et al, 1980;Ennis and Davies, 1982;Wong et al, 1982;Walker 1980Walker , 1983Ostrander et al 1985). These proliferative lesions may progress to uterine adenocarcinoma (Rustia and Shubik, 1976;Napalkov and Anisimov, 1979;Vorherr et al, 1979;McLachlan et al, 1980;Gilloteaux et al, 1982;Walker, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…ADL appeared in mice at a high incidence following neonatal treatment with DES (12,14), but seldom occurred in mice exposed prenatally to DES (1 6, 18). Abnormal uterine changes were observed in mice given injections of natural and synthetic estrogens or androgens during the neonatal period (19)(20)(21), but none of the previous studies demonstrated uterine changes at early postnatal ages in mice exposed prenatally to sex hormones, The present study, therefore, was aimed at examining the vaginal and uterine responses to prenatally and neonatally administered DES.…”
mentioning
confidence: 98%